Juventude contemporânea no contexto da ruralidade: um estudo sobre jovens estudantes de Bela Vista de Goiás - Ferreira, Lorrany dos Santos (2019)
The objective of this research is to study about contemporary young people in their rural contexts. In general, we seek to understand how these, whether from urban or rural origins, experience the cultural aspects of the rural universe presented, especially in the city in a “modern” perspective, where they are characterized as “agroboys” and “agrogirls” and are influenced by the US country and the Brazilian cultural industry. From this perspective, we sought to understand the identifications of these youngsters regarding family farming and agribusiness. Thus, through research, we seek to identify their conceptions and imaginary about the countryside and the city, the relationship with work, its origins, leisure practices and future professional perspectives. In this work, young high school students from CEPI Pedro Vieira Januário were surveyed in Bela Vista de Goiás. This municipality is considered as part of the metropolitan region of Goiânia due to its proximity to the capital, but its economic base is the agricultural activities. However, it was in this municipality of agrarian and rural bases that emerged one of the representatives of the goian caipira culture, the storyteller Geraldo Nogueira (“Geraldinho”). Considering this, the research sought to make a historical path of the "modernization" of Goiás and to establish the social representations that stigmatize the rural subjects of "rustic" and "backward".